Analisis Strategi Kesuksesan Kampung Digital Krandegan dalam Mendukung Program Smart Village: Analysis of the Success Strategy of Krandegan Digital Village in Supporting the Smart Village Program - Nur Saidah; Lailatul Khasanah; Asriyatuzzahra; Siti Ridloah (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2022)
Krandegan Digital Village is an example of a smart village, which proved to be able to rise from desolate. The village started from a poor status and turned into the first independent village in Purworejo Regency through optimizing digitalization, especially in the fields of economy and efficiency. Krandegan as a pioneer of the digital-based village in Purworejo has been successful in many proud achievements. However, Krandegan's success cannot be separated from various obstacles faced previously. This study aims to explore what are the obstacles and the key to success of Krandegan Digital Village in supporting the Smart Village program. This research used a qualitative clustering method through a network of ideas using the Wordle program. The result of this research found that Krandegan Village implementation constraints have several important points, namely mindset, needs, interests, application development, socialization, and digital literacy. Meanwhile, the success of the Krandegan Digital Village is influenced by several important factors, including transparency, institutions, human resources, leadership, and thinking strategies. This study provides important information about the transformation of an underdeveloped village into a smart village.